Analisis Pengaruh Desain Kumparan 6-Fasa Terhadap Torsi Dan Kecepatan Motor Induksi 3-Fasa Berbasis Desain 3 Fasa Ganda Tak Simetris - Zuriman Anthony; Ica Laras Widia; Erhaneli Erhaneli; Arfita Yuana Dewi Putra; Andi Syofian (Elkom: Jurnal Elektronika dan Komputer, 2024)
This study aims to examine the impact of a 6-phase design using an asymmetrical dual 3-phase design on the torque and speed of an induction motor, where the newly designed motor still uses a 3-phase power source. The research compares the performance of a conventional 3-phase induction motor with that of an asymmetrical 6-phase induction motor design, focusing on torque and speed. This motor is only designed in terms of its windings, so the motor's position remains unchanged. The 3-phase system applied to the 6-phase induction motor design ensures that the 6-phase motor operates within a 3-phase system. The study also explores performance improvements, particularly in torque and speed, by redesigning the windings of a 3-phase induction motor into an asymmetrical 6-phase motor. The induction motor used in this research has the following specifications: 3-phase, 2 A, 1390 RPM, 50Hz, 0.75 kW, and 380Y. The study aims to understand the effects of the asymmetrical 6-phase induction motor design, particularly regarding torque and speed. The results show that the torque and speed of the two motors differ due to the asymmetrical 6-phase winding design. In a conventional 3-phase induction motor, the winding coil layer distance is 120°, whereas, in the asymmetrical 6-phase induction motor, the distance between the first and second layers is 30°. Based on this analysis, the asymmetrical 6-phase induction motor design demonstrates better performance compared to the conventional 3-phase induction motor.